Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.3319/tao.2004.15.5.925(adse)
|View full text |Cite
|
Sign up to set email alerts
|

Metal Compositions of PM10 and PM2.5 Aerosols in Taipei during Spring, 2002

Abstract: ABSTRACT1 Research Center for Environmental Changes, Academia Sinica, Taipei, Taiwan, ROC.* Corresponding author address: Dr. Shih-Chieh Hsu, Research Center for Environmental Changes, Academia Sinica, Taipei, Taiwan, ROC; E-mail: schsu@rcec.sinica.edu.tw Ambient aerosols, collected in Taipei in spring 2002, were measured for concentrations of 15 metals (Al, Ca, Na, Mg, K, Ti, Sr, Ba, Mn, Co, Zn, Pb, Cu, Cd, and Sb). Al was used as a mineral aerosol particle indicator, and based on temporal variations of Al co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…While Asian dust storms frequently invade North Taiwan, they seldom arrived in South Taiwan during recent decades (Liu 2002;Wang et al 2002;Lung et al 2004;Hsu et al 2004). Yellow rain episodes were reported in Japan and Taiwan at the end of March 2000 (Sun 2000;Ma et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While Asian dust storms frequently invade North Taiwan, they seldom arrived in South Taiwan during recent decades (Liu 2002;Wang et al 2002;Lung et al 2004;Hsu et al 2004). Yellow rain episodes were reported in Japan and Taiwan at the end of March 2000 (Sun 2000;Ma et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that east Taiwan Strait and Japan are also influenced by Asian dust storm to a certain extent, but much weaker than that of Beijing and Qingdao (Hsu et al, 2004(Hsu et al, , 2005Mori et al, 2003). Thus, Fe concentration in Qingdao is less than that in Beijing but higher than that in the other coastal cities (Fig.…”
Section: The Comparison Of the Daily Elemental Concentrations Of Aeromentioning
confidence: 94%
“…These atmospheric contaminants are apparently influenced by local pollution emissions in summer and by long-range transported dust from the Chinese mainland in spring (Hsu et al, 2005(Hsu et al, , 2006. However, only a few researches were focused on elemental characteristic of oceanic aerosols in Xiamen (e.g., Chen et al, 1999;Hsu et al, 2004Hsu et al, , 2005Hsu et al, , 2006. In the Western Taiwan Strait, the early studies which paid attention on airborne elemental concentrations such as Al, Pb, Cu, Cd, etc., were carried out in 1991-1993 (Chen et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…The PTFE filter samples were also used for ionic species and crustal element analyses. The details of the chemical analyses are presented in separate papers in this special issue (Hsu et al 2004;Lung et al 2004). Besides, a redundant sample set was collected on pre-fired quartz filters for analyzing carbonaceous species (i.e., organic carbon and elemental carbon) in aerosols.…”
Section: Field Campaign and Datasetmentioning
confidence: 99%